Performance analysis of the flip turn in swimming: The relationship between pressures and performance times - Clephas, C.; Forster, M.; Stergiou, P.; Katz, L. (Journal of Human Sport & Exercise, 2022)
This study examined the effects of pressure and other kinetic variables on freestyle flip turn performance. It was hypothesized that an increase in average and peak pressure, and a decrease in the magnitude difference between left and right foot pressure, would result in an improved performance of a swimmer as they performed a flip turn. Ten University level (varsity) swimmers performed five freestyle flip turns using their competition technique. Data were collected from a pressure pad mounted to the vertical wall of the pool and from an underwater camera in the sagittal plane. A negative correlation of .58 and .67 was seen for average and peak pressures respectively when compared to five-meter performance times. Average contact area throughout the push-off phase compared to average and maximum load was .94 and .88. An increase in average contact area from 40 cm2 to 50 cm2 resulted in a 26% increase in maximum load. No difference in performance was seen for varying maximum knee flexion angles. Differences between pressure magnitudes between left and right foot did not impact the five-meter performance time. Therefore, increased average contact area throughout the push-off phase caused higher average and maximum loads, and to a lesser extent average and peak pressures. Increases in pressure and load resulted in an improved five-meter performance time. It is concluded that flip turn performance increases through higher contact area with the feet when pushing off the wall.